2018
DOI: 10.1111/inm.12487
|View full text |Cite
|
Sign up to set email alerts
|

Our Sunshine place: A collective narrative and reflection on the experiences of a mental health crisis leading to an admission to a psychiatric inpatient unit

Abstract: Acute mental health inpatient units are complex environments where tensions between clinical and personal recovery can be amplified. The focus for mental health staff is often centred on providing clinical care, whereas from the patient perspective, the admission can represent a profound existential crisis. There are very few user‐led accounts of their experiences of psychiatric inpatient unit. This project was developed in the traditions of Analytic Auto‐Ethnography, a research methodology which provides a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Wyder et al. (2018) found that when consumers felt safe in an acute unit, their experience of recovery was enhanced. Alternately, when consumers felt unsafe, their recovery is likely to be disrupted (Muir‐Cochrane, Oster, Grotto, Gerace, & Jones, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wyder et al. (2018) found that when consumers felt safe in an acute unit, their experience of recovery was enhanced. Alternately, when consumers felt unsafe, their recovery is likely to be disrupted (Muir‐Cochrane, Oster, Grotto, Gerace, & Jones, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other narratives, hospitalization represents a traumatic event (Wyder et al . ) that is often associated with physical restraint and the worsening of the mental health condition. Furthermore, MCC users proposed to assess a reduction in the use of psychiatric medications as another quantitative measure.…”
Section: Quantitative Studymentioning
confidence: 99%